Injuries presenting to an Australian sports medicine centre: a 12-month study - Baquie, P.; Brukner, P. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: To document the conditions seen by medical practitioners at a multidisciplinary sports medicine clinic during a 12-month period on the basis of site of injury, pathology, and sport played. DESIGN: A coding system for anatomical region, pathology, and sport played was designed. PATIENTS: The total number of patient diagnoses coded and entered for analysis was 2,429. RESULTS: The most common sports involved were Australian football 322 (13.3%), distance running 299 (12.3%), netball/basketball 210 (8.6%), racquet sports 140 (5.8%), and track running 135 (5.6%). The most commonly injured region was the knee with 668 presentations (27.5%), followed by the upper limb (8.8%). The most frequently diagnosed pathology was overuse/inflammation with 1,115 (45.9%). Other pathologies diagnosed were partial ligament sprains 316 (13.0%), muscle strain 99 (4.1%), compartment syndrome 85 (3.5%), and third-degree ligament tear (3.5%). The most common diagnoses seen were patellofemoral syndrome, lumbar spine disorders, rotator cuff tendinitis, lateral ligament ankle sprain, medial meniscus tear, medial collateral ligament knee sprain, lateral meniscus tear, achilles tendinosis, anterior cruciate ligament tear and sacroiliac joint inflammation. CONCLUSION: A study of this nature provides valuable information both to the epidemiologist and clinician.